Characteristic alterations of quantity and quality of soil organic matter caused by forest fires in continental Mediterranean ecosystems: a solid-state 13C NMR study - Knicker, H; Almendros, G; González-Vila, F J; González-Pérez, J A; Polvillo, O (European Journal of Soil Science, 2006)
The variable effect of different types of forest fires on the quantity and quality of soil organic matter (SOM) was analysed by comparing burnt and unburnt soils from six forest ecosystems in central Spain by organic elemental analysis and solid-state 13C nuclear magnetic resonance (NMR) spectroscopy. Whole soil samples were collected 1 to 2 years after the fires and included one site affected by two fires within 2 years. The fire-affected soils showed no common pattern with respect to the amount of additional carbon (Cadd) but at all sites, the fire enhanced the aromatic-C content. The weakest fire intensity resulted in the greatest aromatic-C enrichment factor, EFI(aromatic C) indicating the greatest local accumulation of char. The respective Cadd disclosed an EFI(aromatic C) to EFI(alkyl C) ratio, Bchar, of c.1, which supports a small degree of charring. Extensive combustion and volatilization at stronger fire intensities yielded a decrease of EFI(aromatic C) and an increase in Bchar. These trends are in good agreement with fire intensity and forest fuel combustibility in the various sites and therefore these indices could be used to elucidate the quality and quantity of char input that occurs during and after forest fires. No 13C NMR evidence for substantial inputs from non-charred plant necromass was found for any of the single-burn soils. The large carboxyl-C content of Cadd is evidence of the occurrence of oxidation reactions very shortly after the fire. In comparing the single and double-burn sites, no additional char input was observed for the double-burn site, possibly because of complete combustion of young shrubs and char remains during the second fire. The large O-alkyl-C portion found in Cadd of the double-burn soil is best explained by decreased litter degradation.
Keywords: aromatic C enrichment factor; burnt and unburnt soils; Forest fires; mediterranean ecosystems (voyant); Soil organic matter